A powder metallurgy based martensitic stainless steel and a method for producing the same
Patent Information
- Application Number
- CN202611129952.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-27
AI Technical Summary
然而,在MIM制备工艺中,受粉末颗粒堆积状态、脱脂过程及烧结行为等因素影响,制品通常存在一定的孔隙缺陷,主要为微孔、闭孔等
本发明采用金属注射成型(MIM)技术制备了一种具有高致密度和优异耐腐蚀性能的马氏体不锈钢,其制备原料包括17-4PH不锈钢粉末、增强型粉末等;所述增强型粉末由钼粉、复合氮化钛、硅化镍和Fe-Ni-Si预合金化粉末组成,所述复合氮化钛由纳米级氮化钛和亚微米级氮化钛组成,这些组分通过协同作用,能够提升致密性和耐腐蚀性能;本发明制备的马氏体不锈钢特别适合作为需长期服役于润滑介质、水汽或含盐环境中的传动零件;本发明采用现有成熟的MIM制备工艺制备得到马氏体不锈钢,毋需对常规MIM技术的工艺流程、参数等进行特殊调整,具有良好的工艺兼容性。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of stainless steel materials technology, specifically to a martensitic stainless steel based on powder metallurgy and its preparation method. Background Technology
[0002] Powder metallurgy technology, especially metal injection molding (MIM) technology, has been widely used in the manufacturing of precision metal parts due to its advantages such as high material utilization, good dimensional accuracy, and suitability for mass production. For transmission parts with complex shapes, such as gears and sprockets, MIM technology can achieve high-precision near-net-shape forming, meeting the needs of transmission systems for the fabrication of precision and complex structural components.
[0003] 17-4PH stainless steel, a typical precipitation-hardening martensitic stainless steel, possesses high strength and good corrosion resistance, making it an important raw material for manufacturing high-performance stainless steel parts based on MIM (Metal Injection Molding) technology. However, during the MIM manufacturing process, factors such as powder particle packing, degreasing, and sintering behavior often result in certain porosity defects in the finished products, primarily micropores and closed pores. These porosity defects not only reduce the density of the product but also affect the integrity of the surface passivation film, providing channels for the penetration of corrosive media and thus inducing localized electrochemical corrosion, reducing corrosion resistance. Especially for transmission parts that need to operate for extended periods in lubricating media, moisture, or saline environments, porosity defects can easily become corrosion initiation points, accelerating corrosion propagation and shortening service life.
[0004] In summary, there is an urgent need to provide a martensitic stainless steel with high density and excellent corrosion resistance, which is prepared using 17-4PH stainless steel as the main raw material and MIM technology. Summary of the Invention
[0005] Purpose of the invention: The purpose of this invention is to address the current state of the art by providing a powder metallurgy-based martensitic stainless steel and its preparation method.
[0006] Technical solution: The first aspect relates to a martensitic stainless steel based on powder metallurgy, the raw materials of which include: The invention comprises 17-4PH stainless steel powder, reinforcing powder, and binder; the reinforcing powder is composed of molybdenum powder, composite titanium nitride, nickel silicide, and Fe-Ni-Si pre-alloyed powder; the composite titanium nitride is composed of nano-sized and submicron-sized titanium nitride; nickel silicide (Ni2Si) utilizes its low melting temperature to form a liquid phase with good wettability during vacuum sintering, reducing the interfacial energy between 17-4PH stainless steel powders, enhancing powder reordering and bonding capabilities, and promoting sintering neck formation and pore shrinkage; molybdenum powder (Mo) diffuses to the interface of 17-4PH stainless steel powder at high temperatures through a solid-state diffusion mechanism, improving powder metallurgical bonding, reducing defects, and increasing sintering density; on the other hand, the solid solution strengthening effect of Mo can improve microstructure stability and enhance passivation ability; molybdenum powder achieves a synergistic improvement in densification and corrosion resistance of the martensitic stainless steel prepared by this invention.
[0007] In a preferred embodiment, the weight ratio of the reinforced powder to the 17-4PH stainless steel powder is 4.3-5.3:100.
[0008] In a preferred embodiment, the weight of the binder is 9.2-12.4% of the sum of the weights of the 17-4PH stainless steel powder and the reinforcing powder.
[0009] In a preferred embodiment, the weight ratio of the molybdenum powder, the composite titanium nitride, the nickel silicide, and the Fe-Ni-Si pre-alloyed powder is 5.2-5.8:2.5-5:10-11:6.4-7.1.
[0010] In a preferred embodiment, the weight ratio of the nanoscale titanium nitride to the submicron-scale titanium nitride is 1-1.5:0.5-1.
[0011] In a preferred embodiment, the average particle size of the 17-4PH stainless steel powder is 10-20µm.
[0012] In a preferred embodiment, the particle size of the molybdenum powder is 1-5µm.
[0013] In a preferred embodiment, the nickel silicide has a particle size of 1-5µm.
[0014] In a preferred embodiment, the nano-sized titanium nitride has a particle size of 10-50 nm; the submicron-sized titanium nitride has a particle size of 0.1-0.2 µm; the composite titanium nitride includes nano-sized TiN and submicron-sized TiN, and the two different sizes of TiN particles play a synergistic role in this invention: nano-sized TiN promotes early bonding and sintering neck formation by improving interfacial activity, while submicron-sized TiN inhibits abnormal grain growth through dispersion strengthening and grain boundary pinning; the micro-nano TiN particle system of this invention achieves regulation of material diffusion, grain evolution, and pore shrinkage behavior, thereby improving compactness.
[0015] In a preferred embodiment, the adhesive is composed of polyoxymethylene, high-density polyethylene, ethylene-vinyl acetate copolymer and stearic acid.
[0016] Preferably, the adhesive is composed of 7.2-7.5 wt% high-density polyethylene, 4.5-5 wt% ethylene-vinyl acetate copolymer, 2-2.5 wt% stearic acid and the balance polyoxymethylene.
[0017] In a preferred embodiment, the Fe-Ni-Si pre-alloyed powder is prepared by the following steps: Reduced iron powder, metallic silicon powder, and nickel powder are ball-milled and mixed, and then the resulting mixed powder is vacuum annealed. The Fe-Ni-Si pre-alloyed powder is composed of ternary elements Fe, Ni, and Si, which can participate in the vacuum sintering process as a uniform alloying unit, reducing local component segregation and uneven shrinkage, and promoting pore closure. At the same time, the Ni and Si elements in the Fe-Ni-Si pre-alloyed powder can undergo elemental interdiffusion with the nickel silicide liquid phase, adjust the liquid phase composition distribution, and further improve the wetting of 17-4PH stainless steel powder.
[0018] Preferably, the particle size of the reduced iron powder, the metallic silicon powder, and the nickel powder is ≤100µm.
[0019] Preferably, the weight ratio of the reduced iron powder, the metallic silicon powder, and the nickel powder is 73-81:12-17:6-8.
[0020] Preferably, the ball milling is carried out in a planetary ball mill.
[0021] Preferably, the ball milling mixing process parameters are a ball-to-material ratio of 25-30:1, a rotation speed of 400-450 r / min, and a time of 20-25 h.
[0022] Preferably, the vacuum annealing is performed by heating to 895-915°C at a heating rate of 10-15°C / min under an absolute pressure of 0.1 Pa, holding at that temperature for 1-1.5 hours, and then cooling.
[0023] The second aspect relates to a method for preparing martensitic stainless steel based on powder metallurgy, comprising the following steps: The 17-4PH stainless steel powder, reinforcing powder, and binder are sequentially mixed, granulated, injection molded, degreased, vacuum sintered, solution treated, and aged.
[0024] In a preferred embodiment, the mixing process parameters are: temperature 180-185℃, rotation speed 80-150r / min, and time 30-40min.
[0025] In a preferred embodiment, the injection molding process parameters are an injection speed of 10 cm / s. 3 / s, nozzle temperature 190-195℃, molding pressure 700-900 kgf / cm 2 .
[0026] In a preferred embodiment, the degreasing is performed by catalytic degreasing using steam generated from the vaporization of 98.5 wt% concentrated nitric acid.
[0027] In a preferred embodiment, the vacuum sintering is carried out by first heating to 600-610℃ at a heating rate of 5-8℃ / min under an absolute pressure of <10Pa, holding at that temperature for 1-1.2h, then heating to 1295-1310℃ at a heating rate of 5-8℃ / min, holding at that temperature for 3h, and then cooling.
[0028] In a preferred embodiment, the solution treatment involves heating the temperature to 1025-1060°C at a heating rate of 5-8°C / min under an absolute pressure of <10Pa, holding the temperature for 1 hour, and then oil quenching and cooling to room temperature.
[0029] In a preferred embodiment, the aging treatment involves heating the temperature to 500-510°C at a rate of 5-8°C / min under an absolute pressure of <10Pa, holding the temperature for 3-3.2 hours, and then cooling.
[0030] The beneficial effects of this invention include: This invention utilizes metal injection molding (MIM) technology to prepare a martensitic stainless steel with high density and excellent corrosion resistance. The raw materials include 17-4PH stainless steel powder and reinforcing powder. The reinforcing powder consists of molybdenum powder, composite titanium nitride, nickel silicide, and Fe-Ni-Si pre-alloyed powder. The composite titanium nitride comprises nano-sized and submicron-sized titanium nitride. These components work synergistically to enhance density and corrosion resistance. The martensitic stainless steel prepared by this invention is particularly suitable for transmission parts that need to operate for extended periods in lubricating media, moisture, or saline environments. This invention uses existing mature MIM processes to prepare martensitic stainless steel without requiring special adjustments to the process flow and parameters of conventional MIM technology, exhibiting good process compatibility. Detailed Implementation
[0031] The present invention will be further described in detail below with reference to embodiments, so that those skilled in the art can implement it based on the description.
[0032] It should be understood that terms such as having, including, and comprising as used herein do not exclude the presence or addition of one or more other elements or combinations thereof.
[0033] Example 1 A martensitic stainless steel based on powder metallurgy, the raw materials for preparation include: 17-4PH stainless steel powder with an average particle size of 20µm, reinforcing powder, and binder; the binder consists of 7.2wt% high-density polyethylene (Sinopec 5000S), 4.5wt% ethylene-vinyl acetate copolymer, 2wt% stearic acid, and the balance polyoxymethylene (Delrin). The composition is 100P), with the weight ratio of reinforcing powder and 17-4PH stainless steel powder being 4.3:100. The weight of the binder is 9.2% of the sum of the weights of the 17-4PH stainless steel powder and the reinforcing powder. The reinforcing powder consists of 5.2 parts by weight of molybdenum powder with a particle size of 4µm, 2.5 parts by weight of composite titanium nitride, 10 parts by weight of nickel silicide with a particle size of 5µm, and 6.4 parts by weight of Fe-Ni-Si pre-alloyed powder. The composite titanium nitride consists of 1 part by weight of nano-sized titanium nitride with a particle size of 50nm and 0.5 parts by weight of submicron-sized titanium nitride with a particle size of 0.1µm.
[0034] Fe-Ni-Si pre-alloyed powder was prepared by the following steps: 73 parts by weight of reduced iron powder with a particle size of 100µm, 12 parts by weight of metallic silicon powder with a particle size of 100µm and 6 parts by weight of nickel powder with a particle size of 100µm were ball-milled in a planetary ball mill at a ball-to-powder ratio of 25:1, a rotation speed of 400 r / min and a time of 22 h. The resulting mixed powder was then vacuum annealed in a vacuum annealing furnace (heated to 895℃ at an absolute pressure of 0.1 Pa and a heating rate of 10℃ / min, held for 1 h, and then cooled to room temperature in the furnace).
[0035] A method for preparing martensitic stainless steel based on powder metallurgy includes the following steps: sequentially mixing 17-4PH stainless steel powder, reinforcing powder, and binder (temperature 180℃, rotation speed 100r / min, time 30min), granulating, and injection molding (injection speed 10cm). 3 / s, mold temperature 120℃, nozzle temperature 190℃, holding time 4s, molding pressure 700kgf / cm 2 Degreasing (using 98.5wt% concentrated nitric acid vapor generated by vaporization for catalytic degreasing, degreasing temperature 120℃, degreasing time 3h), vacuum sintering (heating to 600℃ at a heating rate of 5℃ / min under an absolute pressure of 1Pa and holding for 1h, then heating to 1295℃ at a uniform heating rate and holding for 3h, then cooling to room temperature in the furnace), solution treatment (heating to 1025℃ at a heating rate of 5℃ / min under an absolute pressure of 1Pa and holding for 1h, then oil quenching and cooling to room temperature), aging treatment (heating to 500℃ at a heating rate of 8℃ / min under an absolute pressure of 5Pa and holding for 3h, then cooling to room temperature in the furnace).
[0036] Example 2 A martensitic stainless steel based on powder metallurgy, the raw materials for preparation include: 17-4PH stainless steel powder with an average particle size of 10µm, reinforcing powder, and binder; the binder consists of 7.5wt% high-density polyethylene (Sinopec 5000S), 5wt% ethylene-vinyl acetate copolymer, 2.5wt% stearic acid, and the balance polyoxymethylene (Delrin). The composition is 100P), with the weight ratio of reinforcing powder and 17-4PH stainless steel powder being 5.3:100, and the weight of the binder being 12.4% of the sum of the weights of the 17-4PH stainless steel powder and the reinforcing powder; the reinforcing powder consists of 5.8 parts by weight of molybdenum powder with a particle size of 5µm, 5 parts by weight of composite titanium nitride, 11 parts by weight of nickel silicide with a particle size of 5µm, and 7.1 parts by weight of Fe-Ni-Si pre-alloyed powder; the composite titanium nitride consists of 1.5 parts by weight of nano-sized titanium nitride with a particle size of 20nm and 1 part by weight of submicron-sized titanium nitride with a particle size of 0.2µm.
[0037] Fe-Ni-Si pre-alloyed powder was prepared by the following steps: 81 parts by weight of reduced iron powder with a particle size of 80µm, 17 parts by weight of metallic silicon powder with a particle size of 80µm and 8 parts by weight of nickel powder with a particle size of 80µm were ball-milled in a planetary ball mill at a ball-to-powder ratio of 30:1, a rotation speed of 450 r / min and a time of 25 h. The resulting mixed powder was then vacuum annealed in a vacuum annealing furnace (heated to 915℃ at a heating rate of 15℃ / min under an absolute pressure of 0.1Pa and held for 1.5 h, then cooled to room temperature with the furnace).
[0038] A method for preparing martensitic stainless steel based on powder metallurgy includes the following steps: sequentially mixing 17-4PH stainless steel powder, reinforcing powder, and binder (temperature 185℃, rotation speed 150r / min, time 40min), granulating, and injection molding (injection speed 10cm). 3 / s, mold temperature 120℃, nozzle temperature 195℃, holding time 4s, molding pressure 900kgf / cm 2 ), degreasing (using 98.5wt% concentrated nitric acid vapor generated by vaporization for catalytic degreasing, degreasing temperature 120℃, degreasing time 3h), vacuum sintering (heating to 610℃ at a heating rate of 5℃ / min under an absolute pressure of 2Pa and holding for 1.2h, then heating to 1310℃ at a uniform heating rate and holding for 3h, then cooling to room temperature in the furnace), solution treatment (heating to 1060℃ at a heating rate of 5℃ / min under an absolute pressure of 2Pa and holding for 1h, then oil quenching and cooling to room temperature), aging treatment (heating to 510℃ at a heating rate of 7℃ / min under an absolute pressure of 5Pa and holding for 3.2h, then cooling to room temperature in the furnace).
[0039] Example 3 A martensitic stainless steel based on powder metallurgy, the raw materials for preparation include: 17-4PH stainless steel powder with an average particle size of 15µm, reinforcing powder, and binder; the binder consists of 7.3wt% high-density polyethylene (Sinopec 5000S), 4.6wt% ethylene-vinyl acetate copolymer, 2.4wt% stearic acid, and the balance polyoxymethylene (Delrin). The composition is 100P), with the weight ratio of reinforcing powder and 17-4PH stainless steel powder being 4.9:100, and the weight of the binder being 10.5% of the sum of the weights of the 17-4PH stainless steel powder and the reinforcing powder; the reinforcing powder consists of 5.3 parts by weight of molybdenum powder with a particle size of 2µm, 4 parts by weight of composite titanium nitride, 10 parts by weight of nickel silicide with a particle size of 2µm, and 7 parts by weight of Fe-Ni-Si pre-alloyed powder; the composite titanium nitride consists of 1.2 parts by weight of nano-sized titanium nitride with a particle size of 40nm and 0.6 parts by weight of submicron-sized titanium nitride with a particle size of 0.2µm.
[0040] Fe-Ni-Si pre-alloyed powder was prepared by the following steps: 80 parts by weight of reduced iron powder with a particle size of 100µm, 13 parts by weight of metallic silicon powder with a particle size of 100µm and 6.5 parts by weight of nickel powder with a particle size of 100µm were ball-milled in a planetary ball mill at a ball-to-powder ratio of 28:1, a rotation speed of 400 r / min and a time of 24 h. The resulting mixed powder was then vacuum annealed in a vacuum annealing furnace (heated to 905℃ at a heating rate of 10℃ / min under an absolute pressure of 0.1Pa and held for 1 h, then cooled to room temperature with the furnace).
[0041] A method for preparing martensitic stainless steel based on powder metallurgy includes the following steps: sequentially mixing 17-4PH stainless steel powder, reinforcing powder, and binder (temperature 185℃, rotation speed 100 r / min, time 30 min), granulating, and injection molding (injection speed 10 cm). 3 / s, mold temperature 120℃, nozzle temperature 195℃, holding time 4s, molding pressure 850kgf / cm 2 Degreasing (using 98.5wt% concentrated nitric acid vapor generated by vaporization for catalytic degreasing, degreasing temperature 120℃, degreasing time 3h), vacuum sintering (heating to 600℃ at a heating rate of 5℃ / min under an absolute pressure of 1Pa and holding for 1h, then heating to 1300℃ at a uniform heating rate and holding for 3h, then cooling to room temperature with the furnace), solution treatment (heating to 1050℃ at a heating rate of 5℃ / min under an absolute pressure of 1Pa and holding for 1h, then oil quenching and cooling to room temperature), aging treatment (heating to 500℃ at a heating rate of 5℃ / min under an absolute pressure of 5Pa and holding for 3h, then cooling to room temperature with the furnace).
[0042] Example 4 A martensitic stainless steel based on powder metallurgy, the raw materials for preparation include: 17-4PH stainless steel powder with an average particle size of 15µm, reinforcing powder, and binder; the binder consists of 7.4wt% high-density polyethylene (Sinopec 5000S), 4.5wt% ethylene-vinyl acetate copolymer, 2wt% stearic acid, and the balance polyoxymethylene (Delrin). The composition is 100P), with the weight ratio of reinforcing powder and 17-4PH stainless steel powder being 4.5:100, and the weight of the binder being 9.5% of the sum of the weights of the 17-4PH stainless steel powder and the reinforcing powder; the reinforcing powder consists of 5.7 parts by weight of molybdenum powder with a particle size of 1µm, 4.5 parts by weight of composite titanium nitride, 11 parts by weight of nickel silicide with a particle size of 1µm, and 6.8 parts by weight of Fe-Ni-Si pre-alloyed powder; the composite titanium nitride consists of 1.4 parts by weight of nano-sized titanium nitride with a particle size of 10nm and 1 part by weight of submicron-sized titanium nitride with a particle size of 0.2µm.
[0043] Fe-Ni-Si pre-alloyed powder was prepared by the following steps: 75 parts by weight of reduced iron powder with a particle size of 100µm, 13 parts by weight of metallic silicon powder with a particle size of 100µm and 7 parts by weight of nickel powder with a particle size of 100µm were ball-milled in a planetary ball mill at a ball-to-powder ratio of 25:1, a rotation speed of 450 r / min and a time of 24 h. The resulting mixed powder was then vacuum annealed in a vacuum annealing furnace (heated to 915℃ at an absolute pressure of 0.1 Pa and a heating rate of 12℃ / min, held for 1 h, and then cooled to room temperature with the furnace).
[0044] A method for preparing martensitic stainless steel based on powder metallurgy includes the following steps: sequentially mixing 17-4PH stainless steel powder, reinforcing powder, and binder (temperature 180℃, rotation speed 150 r / min, time 40 min), granulating, and injection molding (injection speed 10 cm). 3 / s, mold temperature 120℃, nozzle temperature 195℃, holding time 4s, molding pressure 900kgf / cm 2 Degreasing (using 98.5wt% concentrated nitric acid vapor generated by vaporization for catalytic degreasing, degreasing temperature 120℃, degreasing time 3h), vacuum sintering (heating to 600℃ at a heating rate of 7℃ / min under an absolute pressure of 1Pa and holding for 1.2h, then heating to 1295℃ at a uniform heating rate and holding for 3h, then cooling to room temperature in the furnace), solution treatment (heating to 1030℃ at a heating rate of 8℃ / min under an absolute pressure of 1Pa and holding for 1h, then oil quenching and cooling to room temperature), aging treatment (heating to 505℃ at a heating rate of 5℃ / min under an absolute pressure of 1Pa and holding for 3h, then cooling to room temperature in the furnace).
[0045] Comparative Example 1 Martensitic stainless steel was prepared using the same method as in Example 3, with the only difference being: The reinforced powder consists of 4 parts by weight of composite titanium nitride, 10 parts by weight of nickel silicide with a particle size of 2µm, and 7 parts by weight of Fe-Ni-Si pre-alloyed powder.
[0046] Comparative Example 2 Martensitic stainless steel was prepared using the same method as in Example 3, with the only difference being: The reinforced powder consists of 5.3 parts by weight of molybdenum powder with a particle size of 2µm, 10 parts by weight of nickel silicide with a particle size of 2µm, and 7 parts by weight of Fe-Ni-Si pre-alloyed powder.
[0047] Comparative Example 3 Martensitic stainless steel was prepared using the same method as in Example 3, with the only difference being: The reinforced powder consists of 5.3 parts by weight of molybdenum powder with a particle size of 2µm, 4 parts by weight of composite titanium nitride, and 7 parts by weight of Fe-Ni-Si pre-alloyed powder.
[0048] Comparative Example 4 Martensitic stainless steel was prepared using the same method as in Example 3, with the only difference being: The reinforced powder consists of 5.3 parts by weight of molybdenum powder with a particle size of 2µm, 4 parts by weight of composite titanium nitride, and 10 parts by weight of nickel silicide with a particle size of 2µm.
[0049] Comparative Example 5 Martensitic stainless steel was prepared using the same method as in Example 3, with the only difference being: The reinforced powder consists of 5.3 parts by weight of molybdenum powder with a particle size of 2µm, 4 parts by weight of nano-sized titanium nitride with a particle size of 40nm, 10 parts by weight of nickel silicide with a particle size of 2µm, and 7 parts by weight of Fe-Ni-Si pre-alloyed powder.
[0050] Comparative Example 6 Martensitic stainless steel was prepared using the same method as in Example 3, with the only difference being: The reinforced powder consists of 5.3 parts by weight of molybdenum powder with a particle size of 2µm, 4 parts by weight of submicron titanium nitride with a particle size of 0.2µm, 10 parts by weight of nickel silicide with a particle size of 2µm, and 7 parts by weight of Fe-Ni-Si pre-alloyed powder.
[0051] Comparative Example 7 Martensitic stainless steel was prepared using the same method as in Example 3, with the only difference being: The reinforcing powder was replaced by an equal weight of 17-4PH stainless steel powder with an average particle size of 15µm.
[0052] Test Example 1 The density of the martensitic stainless steels prepared in Examples 1-4 and Comparative Examples 1-7 was tested according to the Archimedes method, and the theoretical density was calculated based on the formula to obtain the relative density.
[0053] Table 1. Relative Density Test Example 2 The martensitic stainless steels prepared in Examples 1-4 and Comparative Examples 1-7 were subjected to electrochemical tests in 3.5wt% NaCl solution. After the open circuit potential stabilized, the self-corrosion potential (Ecorr) was recorded. The test adopted a three-electrode system with a saturated calomel electrode (SCE) as the reference electrode, and the test temperature was 25±1℃.
[0054] Table 2. Self-corrosion potential Based on the relative density and self-corrosion potential test results in Tables 1 and 2, it can be seen that the martensitic stainless steel prepared by this invention has a higher relative density, a denser microstructure, and a higher self-corrosion potential, indicating that its corrosion resistance is enhanced.
[0055] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details.
Claims
1. A martensitic stainless steel based on powder metallurgy, characterized in that, The raw materials for preparation include: 17-4PH stainless steel powder, reinforcing powder, and binder; the reinforcing powder is composed of molybdenum powder, composite titanium nitride, nickel silicide, and Fe-Ni-Si pre-alloyed powder; the composite titanium nitride is composed of nano-sized titanium nitride and submicron-sized titanium nitride.
2. The martensitic stainless steel based on powder metallurgy according to claim 1, characterized in that, The weight ratio of the reinforced powder to the 17-4PH stainless steel powder is 4.3-5.3:
100.
3. The martensitic stainless steel based on powder metallurgy according to claim 1, characterized in that, The weight ratio of the molybdenum powder, the composite titanium nitride, the nickel silicide, and the Fe-Ni-Si pre-alloyed powder is 5.2-5.8:2.5-5:10-11:6.4-7.
1.
4. The martensitic stainless steel based on powder metallurgy according to claim 1, characterized in that, The weight ratio of the nanoscale titanium nitride to the submicron-scale titanium nitride is 1-1.5:0.5-1.
5. The martensitic stainless steel based on powder metallurgy according to claim 1, characterized in that, The nanoscale titanium nitride has a particle size of 10-50 nm; the submicron-scale titanium nitride has a particle size of 0.1-0.2 µm.
6. The martensitic stainless steel based on powder metallurgy according to claim 1, characterized in that, The adhesive is composed of polyoxymethylene, high-density polyethylene, ethylene-vinyl acetate copolymer and stearic acid.
7. A martensitic stainless steel based on powder metallurgy according to claim 1, characterized in that, The Fe-Ni-Si pre-alloyed powder is prepared by the following steps: Reduced iron powder, metallic silicon powder, and nickel powder are ball-milled and mixed, and then the resulting mixed powder is vacuum annealed.
8. A martensitic stainless steel based on powder metallurgy according to claim 7, characterized in that, The weight ratio of the reduced iron powder, the metallic silicon powder, and the nickel powder is 73-81:12-17:6-8.
9. A martensitic stainless steel based on powder metallurgy according to claim 7, characterized in that, The ball milling process parameters are: ball-to-material ratio 25-30:1, rotation speed 400-450 r / min, and time 20-25 h.
10. A method for preparing martensitic stainless steel based on powder metallurgy according to any one of claims 1-9, characterized in that, Includes the following steps: The 17-4PH stainless steel powder, reinforcing powder, and binder are sequentially mixed, granulated, injection molded, degreased, vacuum sintered, solution treated, and aged.